Pengaruh Pemberian Ekstrak Bunga Mawar Merah (Rosa Damascena Mill.) Terhadap Morfologi Sel Ginjal Pada Tikus Putih Galur Wistar (Rattus Norvegicus) Yang Diinduksi Karbon Tetraklorida (CCl4). - Amdat, Muhammad Khozaainul Saddam; , Dr. Retno Sintowati, M.Sc; , Riandini Aisyah, S.Si, M.Sc (2017)
Background: Tetrachloride Carbon (CCl4) is subtance that can trigger free radicals. Free radicals formed as aerobic metabolism's normal result, but they can increase at pathological conditions, because there is an imbalance between the free radicals by the body's natural antioxidant. CCl4 causes Acute Tubular Necrosis with the pathologydescriotion in the kidney. Red rose (Rosa damascena Mill.) contains antioxidant. Purpose: to find out the effect of red rose extract (Rosa damascena Mill.) on kidney cell morphology of Galur Wistar Mice (Rattus norvegicus) induced with Tetrachloride Carbon (CCl4). Method: Mice were divide in 5 groups, each 5 mice were treat in different treatments, that are in negative control, in positive control (induced CCl4), P1 (induced CCl4 and red rose extract 250mg), P2 (induced CCl4 and red rose extract 500mg), P3 (induced CCl4 and red rose extract 1000mg). CCl4 was given subcutaneousty in every 7 days and red rose extract was given orally every day during 14 days. After that mice were dissected, their kidneys were made as histology preparation by HE colouring. The result was processed by using One Way Anova test. Result: The result of Kruskal Wallis test on red rose extract shows the total scores of yhe right kidney cell damage is p=0,000. As score (p<0,05), so there is a significant difference. Conclusion: By giving red rose extract in I, II, and III (250mg, 500mg, and 1000mg) during 14 days can repair the morfologi glomerulus cell in damage of Wistar Mice's kidney induced withTetrachloride Carbon (CCl4). Keywords: Red Rose, CCl4, Morfologi, Antioxidant